Building the European capacity in operational oceanography : proceedings of the Third International Conference on EuroGOOS : 3-6 December, 2002, Athens, Greece - Dahlin, H. (Elsevier, 2003)
This proceedings 3rd EuroGOOS Conference on Building the European Capacity in Operational Oceanography is volume 69 in the Elsevier Oceanography Series. The topics of the proceedings cover: Regional Systems I, Remote Sensing Systems, Numerical Modelling and Data Assimilation, Next Generation Systems, EC Operational Forecasting Workshop: Reports on EC Operational Forecasting, In-Situ Monitoring, Waves Monitoring and ForecastingUser Perspectives, EuroGOOS Task Teams, Regional Systems 2, Coastal Systems, Data - Products - Users, and GMES Marine Forum.
Keywords: Oceanography -- Remote sensing -- Congresses.; Oceanography -- Europe -- Congresses.; elektronické knihy; electronic books